Evaluation of Students' Conceptual Understanding of Malaria - Cheong, I.; Treagust, David; Kyeleve, I.; Oh, P. (Routledge, 2010)
In this study, a two‐tier diagnostic test for understanding malaria was developed and administered to 314 Bruneian students in Year 12 and in a nursing diploma course. The validity, reliability, difficulty level, discriminant indices, and reading ability of the test were examined and found to be acceptable in terms of measuring students' understanding and identifying alternative conceptions with respect to malaria. Results showed that students' understanding of malaria was high for content, low for reasons, and limited and superficial for both content and reasons. The instrument revealed several common alternative conceptual understandings students' hold about malaria. The MalariaTT2 instrument developed could be used in classroom lessons for challenging alternative conceptions and enhancing conceptions of malaria.